Conceptualizing Public Finance Research in the Context of the Azerbaijani Economy Via Expert Interviews - Ibrahim Niftiyev (SSRN, 2024)
Public finance is a vital area of study that helps governments make informed decisions about how to raise and allocate funds to finance their activities, ultimately contributing to the well-being of society. Oil-rich developing and emerging economies present a distinct set of public finance realities. While they may enjoy substantial revenue streams from oil exports, this dependence creates unique challenges. This fact should have stimulated academic research to thoroughly analyze public finance, but it seems that there is not enough work in Azerbaijan that accurately captures the current challenges and proposes sound policy solutions in public finance sphere. Most of the studies are practice-oriented and written by international organizations (i.e., policy briefs, expert opinions) rather than local experts who could communicate them to a wider societal audience. This discussion paper draws some conclusions from the expert interviews on the problems and challenges in the field of public finance, the quality of research conducted in this field and future directions in the field of public finance in the case study of Azerbaijan. Briefly, the experts pointed out that the current state of research in the field of public finance is inadequate and highlighted some key problems such as inefficiency, transparency and dependence on the extractive industry in public finance. This discussion paper also provides some possible future research directions in the field of public finance in relation to Azerbaijan. This paper is not a conclusive study, but a conceptualization of the mentioned direction in the literature. The findings should be in the interest of policy makers and researchers working intensively on public finance issues in Azerbaijan.
Keywords: H11; O10; P10; 330; Azerbaijani economy; expert consultation; fiscal policy; macroeconomic stability; public finance; public policy